Modelling of Corrosion Under Insulation for Piping System - MOHD JAMIL, RASHIDATUNNUR; Md Salleh, Salihatun (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Corrosion under insulation (CUI) is the external corrosion on the surface of pipe, carbon manganese steel, or austenitic stainless steel that occurs beneath insulation as a result of water penetration. CUI is one of the most severe types of corrosion, defined by electrochemical deterioration of an alloy or metal when insulated. CUI existed when there was water and oxygen on the steel surface, and the corrosion rate was determined by the type of insulation, the chemical composition of the water, the availability of oxygen, and the temperature. The goal of this examination is to use a time-based series to detect and monitor the quantity of water intrusion absorbed in the insulating material. This monitoring inspection is carried out by putting in the pipe system in the UTHM region. The AR, ARX, and ARMAX models were built using 150 data points. When compared to the AR and ARX models, the ARMAX model with parameter (12, 11) yields the best results, with an MSE reading of 0.06627 and FPE of 0.1066. As a consequence of this research, we can conclude that the ARMAX model is more practical and accurate than the other models for detecting water ingress in a pipe system.